Edu-Tax21: Integrasi Program Pembelajaran Pajak dengan Keterampilan TIK di Perguruan Tinggi - Sheila Febriani Putri; Hanjar Ikrima Nanda; Anin Dyah Luthfiani; Slamet Fauzan (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to provide an effective learning system from technology-based taxation practicum. The learning videos uploaded to MOOC are the material studied in this case study research. The data taken are interviews with expert validators and also students who are taking taxation practicum. Furthermore, the results are triangulated with the value of the assignment before and after using the learning video. The results of the analysis show that using e-learning provided by publishers is not enough to help students learn tax practicum well. The e-learning content presented by publishers is still conventional, namely pdf files related to cases and also working paper files in the form of excel which can be downloaded. Students still feel confused about the flow of work. Meanwhile, after accessing the video, students feel more independent in doing e-learning tax practicum. Interaction with technology makes it easier for students to do tax practicum.